2014
DOI: 10.1002/adsc.201400369
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Cross‐Coupling of Organozinc Halides with Bromoalkynes

Abstract: The cobalt-catalyzed cross-coupling of organozinc bromides is described. In the case of arylzinc reagents, the same cobalt catalyst, CoBr 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…First, the high reactivity of bromoalkynes could pose a selectivity problem. [9] Second, the low steric bulk of the alkyne could lead to rapid transmetalation and homocoupling to form diynes. Finally, alkynes can act as radical acceptors and strong ligands, potentially leading to catalyst inhibition and side reactions.…”
mentioning
confidence: 99%
“…First, the high reactivity of bromoalkynes could pose a selectivity problem. [9] Second, the low steric bulk of the alkyne could lead to rapid transmetalation and homocoupling to form diynes. Finally, alkynes can act as radical acceptors and strong ligands, potentially leading to catalyst inhibition and side reactions.…”
mentioning
confidence: 99%
“…In 2014, Gosmini et al reported as hort review on the recent advances in electrophilica mination reactions, includingp art of the R 2 NÀOBz involvedr eactions. [11] However, the electrophilic aminationr eaction, in particular, those using of O-benzoylhydroxylamines as amination reagents, has developed rapidly, and several breakthroughsh ave been achieved recently.T hus it is necessary to update the new advances in this field. Herein, we would like to contributeacomprehensive review focusing on transitionmetal-catalyzed electrophilic amination reactions using R 2 NÀ OBz as the electrophilica minating reagent.…”
Section: Introductionmentioning
confidence: 99%
“…The success of an in situ activation protocol and the facile synthesis of the drug molecule (AE)-preclamol highlight the synthetic potential of this method. [8] Inspired by these elegant studies,w e reasoned that al ow-valent cobalt catalyst could also donate an electron to the redox-active ester, [9] thereby triggering alkyl radical formation and af ollow-up cross-coupling reaction.Cobalt, as an earth-abundant and low-toxic first-row transition metal, has been previously identified as an attrac-tive catalyst enabling the effective coupling of aryl, [10] alkenyl, [11] and alkynyl halides [12] (or their pseudohalides) with organozinc compounds (Figure 1a). [1] While organohalides have enjoyed as uccess as the electrophilic coupling partners,r ecent years have witnessed ag rowing interest in the use of aliphatic carboxylic acids (or their derivatives) as alkyl halide surrogates in such reactions.…”
mentioning
confidence: 99%
“…Cobalt, as an earth-abundant and low-toxic first-row transition metal, has been previously identified as an attrac-tive catalyst enabling the effective coupling of aryl, [10] alkenyl, [11] and alkynyl halides [12] (or their pseudohalides) with organozinc compounds (Figure 1a). Nevertheless,t he use of unactivated alkyl electrophiles [13] in cobalt-catalyzed Negishi coupling reactions is only recent.…”
mentioning
confidence: 99%
See 1 more Smart Citation